2019
DOI: 10.1002/elps.201800502
|View full text |Cite
|
Sign up to set email alerts
|

A new stability indicating reverse phase high performance liquid chromatography method for the determination of enantiomeric purity of a DPP‐4 inhibitor drug linagliptin

Abstract: A simple, sensitive, and stability indicating isocratic reverse phase high performance liquid chromatography method has been developed, optimized and validated for the separation and quantification of S-enantiomer in linagliptin (R-enantiomer) drug substance. Enantiomeric separation was achieved on a Cellulose tris(4-chloro-3-methylphenylcarbamate) stationary phase. Mobile phase consists of aqueous diammonium hydrogen phosphate buffer and acetonitrile in the ratio of 35:65 v/v. Isocratic elution was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In addition, some bioanalytical methods were reported for LIN ‐ related to its pharmacology, kinetics and drug interactions 13–16 . There have been a few studies on the stability of LIN alone and in combination with other antidiabetic drugs in formulations using HPLC 17–19 and two reports on the impurity analysis of LIN 20,21 . However, there is no information available on the degradation behavior of LIN.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some bioanalytical methods were reported for LIN ‐ related to its pharmacology, kinetics and drug interactions 13–16 . There have been a few studies on the stability of LIN alone and in combination with other antidiabetic drugs in formulations using HPLC 17–19 and two reports on the impurity analysis of LIN 20,21 . However, there is no information available on the degradation behavior of LIN.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the published HPLC methods [4][5][6][7], the proposed CE method was demonstrated to be an equivalently precise, sensitive, and robust method with reduced running time, thus making it a more convenient routine analysis method. The elution order of the S-enantiomer peak before the large peak of Lina suggested that the CE method is reliable because the small impurity peak is not likely to overlap with the Lina peak.…”
Section: Validation and Applicationmentioning
confidence: 99%
“…Recent chiral drug analyses have mostly been based on HPLC and CE methods. Several chiral HPLC methods have recently been proposed using cellulose-and amylose-based chiral stationary phases for the quantification of S-Lina [4][5][6][7]. The published HPLC methods efficiently resolved Lina enantiomers as well as determined the S-enantiomer content in the bulk drug of Lina.…”
Section: Introductionmentioning
confidence: 99%
“…Enantiomers of drugs often differ in their pharmacological action. Other gliptins such as linagliptin,[ 10 ] alogliptin,[ 11 ] and sitagliptin[ 12 ] and teneligliptin also show chirality. However, with the exception of teneligliptin—all the other gliptins are manufactured by a single company.…”
Section: Drug Quality—things To Considermentioning
confidence: 99%